ANALYSIS OF MODERN MARKETING TRENDS IN CONSTRUCTION INDUSTRY - D. Manukyan (Publishing House of the State University of Management, 2017)
This article describes the features of modern marketing in the construction industry. The main types of marketing strategy are considered. Within the scope of this article features of application of marketing strategies in the construction industry are distinguished. Authors reveals objectives and characteristics of development of marketing plan for a construction company. The universal step-by-step model of development of marketing strategy is given in the construction industry.